Analysis of porous structure in plasma-sprayed coating - Jůzková, Radka (Image analysis and stereology, 2004)
The paper is devoted to the quantitative analysis of the microstructure of a ceramic plasma-sprayed coating. The aim is to describe the size and spatial distribution of approximately convex pores. A whole 3D specimen was subsequently grinded to obtain serial sections of small distance. Using image analysis techniques the centroids and size of individual pores are detected and the obtained data analysed by means of summary spatial statistics. The tests of complete spatial randomness are performed using various 3D characteristics and important practical conclusions for the material fabrication procedure are obtained.
Keywords: Delec, velikost; Steel; Ceramics; Jeklo; Keramika; Particle Size; ceramic; Image Processing, Computer-Assisted; Slika, obdelava z računalnikom; mikrostruktura; poroznost